2018
DOI: 10.1093/zoolinnean/zly021
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of diapause in Rivulus (Laimosemion)

Abstract: Annual killifish that are adapted to life in aquatic habitat that dries seasonally have evolved desiccation-resistant eggs capable of undergoing diapause, i.e. developmental arrest, at specific stages during embryology. Although noted for their remarkable ability to live at the land-water interface, species in the genus Rivulus are considered to be nonannual killifish that exhibit typical teleost developmental patterns and no embryonic diapause. Here, we combine a molecular phylogeny with an embryological stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…One limitation to our microcosm experiment was that fish were unable to disperse. The natural habitat of mangrove rivulus and other rivuline killifishes typically consists of a mosaic of small, intermittent pools (Turko and Wright, 2015;Furness et al, 2018;Sutton et al, 2018). A high metabolic rate is often correlated with high boldness and activity (e.g.…”
Section: Emersion Tolerance Trade-offsmentioning
confidence: 99%
“…One limitation to our microcosm experiment was that fish were unable to disperse. The natural habitat of mangrove rivulus and other rivuline killifishes typically consists of a mosaic of small, intermittent pools (Turko and Wright, 2015;Furness et al, 2018;Sutton et al, 2018). A high metabolic rate is often correlated with high boldness and activity (e.g.…”
Section: Emersion Tolerance Trade-offsmentioning
confidence: 99%
“…Monophyly is supported by molecular analyses (Hrbek et al, 2004;Costa 2011aCosta , 2013. This is considered a non-annual genus; however, Furness et al (2018) have found diapause stages in some species similar to those found in annual species, which could represent intermediates steps in the evolution of the annual life cycle.…”
Section: Systematics Of Rivulidaementioning
confidence: 88%
“…Slowing down during early development in nonannuals in response to desiccation might be mostly an immediate response, therefore quiescence, even while there are some lagged effects (however, see Furness et al, ). If genetic assimilation of diapause has occurred in killifish via the evolution of plasticity in response to desiccation, then there has clearly been further plasticity evolution after the emergence of diapause‐like characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Their plastic hatching delay showed several characteristics of diapause III which is constitutive in annuals. Since then, Furness, Reznick, Tatarenkov, and Avise () showed that developmental properties presumed to be limited to annuals do occur in some sister taxa. For annual killifish, there are no data allowing a detailed analysis of rates of development and survival during and after a desiccation period.…”
Section: Introductionmentioning
confidence: 99%